Provide a secured automatic program algorithm for DNA sequence storage arrangement in cloud - Geetha, G; Surekha, G; Aditya Sharma, P; Uma Shankari, E (International Journal of Engineering and Technology, 2018)
The primary target of this paper is to provide a secured implementing algorithm for hiding DNA sample sequence data confidently by using special software in cloud computing environments. The suggested algorithm here for hiding DNA sequences is based on binary coding and complementary pairing rules. Hence DNA reference sequence is taken as a sample secret data with a notation of M. But after applying some steps the final result obtained in cloud environment is Mâ€™â€™â€™. The procedure of identifying or extracting the original data M from the hidden DNA Reference sequence is depended on the user if and only if the user wants to use the data for process. Likewise there are security issues for the manipulating from claiming information. In this way that accessible userâ€™s information arrangement may be isolated under SPs in such a way that it has to reach minimum number of specified threshold SPs number from the whole data block. In this paper, we recommend A low cost secured and multi- cloud storageÂ (SCMCS) model over cloud computing which holds an prudent appropriation about information Around the accessible SPs in the market, with gatherings gives client information accessibility and additionally secure capacity.Â Â